1990
DOI: 10.1144/gsl.sp.1990.052.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Microbial mediation in phosphatogenesis: new data from the Cretaceous phosphatic chalks of northern France

Abstract: Detailed petrographic study of the Upper Cretaceous phosphatic chalks of northern France, particularly by scanning electron microscopy, shows that phosphate occurs predominantly as phosphatized bacterial remains. Shiny phosphatic crusts on hardgrounds and anisotropic phosphate coatings on grains are interpretated as phosphate mineralized microbial (‘microstromatolitic’) structures. Phosphatic remains of ovoid bacteria and of microbial colonies with botryoidal surfaces have been observed in chambers of foramini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Phosphate matrix corresponding to apatite globules of about 1 μm diameter is also typical ( figure 4H). The globules resemble fossilized microbial cells reported by several workers (Rao and Nair 1988;Lamboy 1990). The crystalline faces of the globules may indicate transformation of initially formed structures.…”
Section: Petrology Of the Cretaceous Phosphoritessupporting
confidence: 75%
“…Phosphate matrix corresponding to apatite globules of about 1 μm diameter is also typical ( figure 4H). The globules resemble fossilized microbial cells reported by several workers (Rao and Nair 1988;Lamboy 1990). The crystalline faces of the globules may indicate transformation of initially formed structures.…”
Section: Petrology Of the Cretaceous Phosphoritessupporting
confidence: 75%
“…Krajewski 1984;Delamette 1988a;FOllmi 1989b;Lamboy 1990. The optimum in preservation of microbial mats is observed in distal areas of the belt of condensation and phosphogenesis, and was probably related to the proximity of the oxygenminimum zone (Fig.…”
Section: Current-induced Condensation and The Presence Of An Oxygen-mmentioning
confidence: 97%
“…However, the controversy still exists as whether the apatite is formed by direct precipitation or by replacement of calcium carbonate. Many workers have concluded that most phosphorite deposits have formed due to accumulation of carbonate fluorapatite formed by the post mortem alteration of phosphorus-rich bacterial cells (O'Brien, et al 1981;Riggs 1982;Prtvtt & Lucas 1986;Lamboy 1990;Lewy 1990). On this basis it can be suggested that microorganisms were responsible for the phosphatized stromatolites of the Jhamarkotra and other deposits, and that mineralization took place preferentially in subtidal areas, in part because here stromatolites only originally contained low-Mg calcite, which was easily transformed into apatite.…”
Section: Discussionmentioning
confidence: 99%